Managing the grazing resource for animal production in savannas of tropical America - Lascano Aguilar, Carlos Eduardo (1991)
Research carried out to evaluate management options and animal production potential of native and improved pastures in savanna regions of tropical America is reviewed, with emphasis on Colombia's Eastern Plains. In areas with limited infrastructure native grasses are the main forage resource and weight gains of cattle grazing these native pastures with burning and mineral supplementation vary from 70 to 90 kg/hd and from 15 to 20 kg/ha. As infrastructure improves, the strategic use of grass-legume pastures to complement the native savanna, together with the use of mineral supplementation, could increase individual weight gains by 40 percent. In savanna areas with good infrastructure, improved grasses adapted to acid soils replace the native vegetation and, together with mineral supplementation and appropriate grazing management, increase animal production/unit area 10 times compared to native pastures. However, these pastures do not persist over time because of N deficiency and pests. The highest and more stable gains could be obtained with legume-based pastures, which, in turn, depend on high management inputs. On the acid soils of tropical American savannas, these legume-based pastures can play an important role in agropastoral systems.